Kinematics and kinetics of double poling with increasing speed in world class cross-country skiers - Lindinger, S.; Stöggl, T.; Müller, E.; Holmberg, H. C. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: During the last decade, double poling (DP) became a main classical technique in cross-country (XC) ski racing. Optimized skiing equipment, better training methods and the sprint discipline led to altered demands and increased focus on DP development. Holmberg et al. (2005) described modern DP characteristics with distinct lower body work, shorter poling times, higher forces and thus a more explosive push-off. So a further question is, how elite skiers control DP speed. Earlier DP studies found increased poling frequencies (Pf) and maintained or decreased cycle lengths (CL) across velocities (Hofmann et al. 1995; Millet et al. 1998; Nilsson et al. 2004) suggesting to primarily adjust Pf as the mechanism of speed control. Besides speed-cycle relationships, no other kinematic and only few kinetic aspects have been analyzed. Purpose of the current study was to perform a detailed analysis of speed increase strategies during DP in modern elite XC skiers.